METHOD FOR DETERMINING THE ACTUAL PRESSURE VALUE IN A MV VACUUM INTERRUPTER - Lech, Michał; Kostyła, Damian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
The paper describes the author’s method for determining the actual pressure value in a vacuum interrupter of a MV disconnector during high-voltage laboratory tests. The need to develop such a method was due to the lack of possibility to measure the pressure directly in the vacuum interrupter during the tests. There was a risk of damaging the vacuum gauge as a result of an electrical jump. The proposed method consists in measuring, in de-energized conditions, the difference in pressure between a set of vacuum pumps and a prototype vacuum interrupter made for the purpose of implementing this method. Thus, knowing the pressure value at the pumps and having the scaling characteristics of the system determined, it will be possible to determine the actual pressure inside the tested MV disconnecting extinguishing interrupter during high-voltage tests. Measurements of pressure drop in the pumping channel were carried out for air and three electro-negative gases: helium, argon and neon, used in the study by the authors of this paper.